Avaliação de capacitação em higiene das mãos por educação a distância - Lima, Regina Silvia Chaves de (2018)
Introduction: Introduction: hand hygiene of health-care workers is the measure with the greatest impact on the effectiveness of prevention and control of infections related to the health-care system. This basic and easily implemented measure has been a worldwide challenge due to its low compliance, despite several strategies made by the World Health Organization. Objectives: the main goal was to evaluate the improvements in hand hygiene of medical students achieved by a DLP. The secondary objectives were to enable medicine students in hand hygiene, to assess hand hygiene training by DLP and to establish a collaboration between the hand hygiene training DLP and the hospital infection control program. Material and method: 99 students of the UNIFEV Medicine course were evaluated through a qualitative and quantitative approach and exploratory methods. The training consisted of six activities, being five online and one on-site. The first was the application of a multiple-choice test with summative evaluation to survey the previous knowledge of the students. The second was carried out through a discussion forum, with a focus on raising the awareness of health professionals to improve compliance – the evaluation was qualitative. In the third a reapplication of the multiple-choice test was performed with automatic feedback by the system. The fourth was practical – the participants analyzed two videos published on the platform. This analysis should be performed in accordance with the eleven steps of the hand hygiene technique recommended by the Brazilian Ministry of Health, identifying the shortcomings in the videos. In the fifth the students had to prepare their own hand sanitation video following the proposed technique – the evaluation included individual feedback. The sixth evaluation was performed on site and carried a Structured Objective Clinical Examination in a simulated situation, in which the student should report the appropriate moments for hand hygiene. Afterwards the students demonstrated the hand hygiene technique and received instantenous individual feedback. Results: among the 99 students enrolled, eight students did not attend (8.1%), 84 students (92.3%; N=91) passed, and seven (7.7%; N=91) failed for not completing all required activities. The first activity presented the average score of 8.00 among all participants. In the second activity, healthcare education and ratings of infection control were the factors with the greatest impact on awareness. Implementing the trainings was the most frequent proposal of the participants to improve awareness. The third, fourth, fifth and sixth activities respectively had average scores of 8.50, 6.50, 9.80 and 9.60 among the students. Conclusion: the participants presented a good performance in the evaluation of previous knowledge, which suggests an adequate theoretical learning in the medicine graduation course. The discussions and reflections were coherent, with feasible proposals, for implementation to improve compliance. The evaluation of handwashing ability initially presented a poor performance, despite the theoretical knowledge being satisfactory. There was a gap between "knowing" and "demonstrating how it is done", revealing the need to implement activities that contemplate the skill of hand hygiene in the curriculum. Several evaluation methods were used, the predominant being the formative evaluation associated with feedback, which contributed to a meaningful learning throughout the training, in which the student demonstrated "how to be done". The modality of DLPs as a fundamental tool in curricular and extracurricular activities should be considered for hand hygiene training as well as its implementation in hospital infection control